Low Back Pain in Resident Doctors with Standardized Training in China: A Cross-Sectional Study - Zhang HW; Tan HP; Feng QX (Risk Management and Healthcare Policy, 2023)
Han-Wen Zhang,1,* Hong-Ping Tan,1,* Qiu-Xia Feng2 1Department of Pain Management, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan Province, People’s Republic of China; 2Outpatient Department, Nanchong Psychosomatic Hospital, Nanchong, Sichuan Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiu-Xia Feng, Outpatient Department, Nanchong Psychosomatic Hospital, Nanchong City, Sichuan Province, People’s Republic of China, Tel +86-(0817) 8010120, Email fengqiuxia@hotmail.comBackground: Low back pain (LBP) is a prevalent occupational disease with high morbidity among healthcare workers. Since the implementation of standardized residency training in China in 2015, the training intensity has significantly increased, which may lead to a higher incidence of LBP. However, epidemiological studies on LBP among resident doctors with standardized training remain scarce.Objective: To investigate the prevalence and associated factors of LBP among resident doctors with standardized training in a tertiary hospital in China.Methods: A cross-sectional study was conducted using self-administered questionnaires to collect information on demographics, lifestyle factors, work-related factors, and LBP from 345 resident doctors. Descriptive statistics were used to analyze the prevalence of LBP. Logistic regression analysis was performed to identify factors associated with LBP.Results: Among 345 participants, the 1-year prevalence of LBP was 75.9%. Multivariable analysis revealed that physical exercise, weekly working hours, and prolonged sitting were independent risk factors for LBP.Conclusion: The prevalence of LBP among resident doctors was high. Promoting physical exercise, controlling working hours, and improving sitting posture may help prevent LBP. The study was limited by its cross-sectional design and self-reported data. Future studies should use longitudinal designs, objective measures, and larger and more representative samples to further explore the epidemiology and etiology of LBP among resident doctors with standardized training.Keywords: low back pain, prevalence, standardized training, resident doctors